Long-Term Outcomes after Double Free Flap Reconstruction for Locally Advanced Head and Neck Cancer - Brinkman, J. Nick; Kambiz, Shoista; de Jong, Tim; Mureau, Marc A. M. (Journal of Reconstructive Microsurgery, 2019)
Background The use of simultaneous, multiple free flaps has become a reliable reconstructive option in patients with extensive composite defects after resection of locally advanced head and neck cancer. However, some reluctance remains among reconstructive surgeons with concerns regarding flap outcomes and limited patient survival. Therefore, we evaluated complications, long-term patient survival, and patient-reported outcomes following these extensive head and neck reconstructions.Methods All consecutive patients treated with multiple free flaps for reconstruction of extensive composite defects after resection of locally advanced head and neck cancer between 1999 and 2014 were retrospectively reviewed. Patient charts were evaluated for demographics, treatment details, complications, and patient survival. In addition, all patients alive at the start of the study were asked to complete the 10-item Eat Assessment Tool (EAT-10) and the Intelligibility Rating Scale (IRS).Results Eighty-four simultaneous, multiple free flaps were performed in 42 patients. The predominant free flap combination consisted of a fibula with either an anterolateral thigh (n = 22) or a radial forearm flap (n = 14). Complete flap survival was 95%. Nineteen patients were still alive with a mean follow-up of 55 months. Five-year patient survival was 46.3%. Mean EAT-10 score was 8.4 (range: 0–29), with only one patient reporting problematic swallowing. Ninety percent of the patients had moderate to good speech intelligibility with the IRS.Conclusion Multiple, simultaneous free flaps can be performed safely, leading to acceptable long-term patient survival and patient-reported functional outcomes. Our study demonstrates that it is worthwhile to perform these challenging microvascular reconstructions in patients with locally advanced head and neck cancer.
Keywords: head and neck; patient-reported outcomes; long-term outcomes